2023
DOI: 10.3390/healthcare11020245
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on COVID-19 Vaccine Hesitancy among the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex and Asexual (LGBTQIA+) Community and Factors Fostering Its Refusal

Abstract: Background: The ramifications of the existing crisis caused by the coronavirus pandemic are sensed in all walks of life. Among the various efforts made to curb the spread of this novel infection, the development of COVID-19 vaccines had a profound role in flattening the pandemic curve. Even though the rapid vaccine drive received a highly welcoming response among people, the reluctance and ignorance of a part of the population towards available safe vaccines stand as impediments to achieving the desired outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
1
8
2
Order By: Relevance
“…In line with the findings of a previous study [ 21 ], we discovered that compared with female sex, male sex was associated with greater MoVAC-19. In addition, older age was positively associated with greater MoVAC-19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with the findings of a previous study [ 21 ], we discovered that compared with female sex, male sex was associated with greater MoVAC-19. In addition, older age was positively associated with greater MoVAC-19.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also identified unique factors associated with MoVAC-19 among LGB individuals. For instance, a review study of 17 articles revealed a cross-sectional association of concerns regarding social stigma due to sexual minority status with reduced intention to get vaccinated against COVID-19 among LGB individuals [ 21 ]. Perceived sexual stigma may prevent LGB individuals from accessing appropriate vaccine knowledge and administration information [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is not limited to the Chinese elderly, but is also a global problem, as survey data reveal it exists across various populations. 6–11 This problem may impedes coverage of vaccination and the establishment of herd immunity, affecting the achievement of anti-pandemic efficacy. 12 Understanding the factors contributing to this hesitancy is essential for developing targeted public health intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the health care experiences of Australian trans people later in the pandemic. Overseas, social stigma, fear of discrimination, and mistrust of health care professionals contributed to COVID‐19 vaccine hesitancy among trans people 9 . Further, trans people often report chronic illness and mood disorders, 4,5,10 both known risk factors for post‐COVID‐19 syndromes (long COVID) 11,12 .…”
mentioning
confidence: 99%
“…Overseas, social stigma, fear of discrimination, and mistrust of health care professionals contributed to COVID‐19 vaccine hesitancy among trans people. 9 Further, trans people often report chronic illness and mood disorders, 4 , 5 , 10 both known risk factors for post‐COVID‐19 syndromes (long COVID). 11 , 12 Disruptions to gender‐affirming health care would also be anticipated, as well as increased discrimination in health care, the result of difficulty in providing training to health care providers in trans‐affirming health care, compounded by COVID‐19‐related priority shifts.…”
mentioning
confidence: 99%